Adolescents' experiences of a theory‐based behavioural intervention for improved oral hygiene: A qualitative interview study. Issue 4 (15th August 2022) - Dimenäs, Sandra L.; Östberg, Anna‐Lena; Lundin, Mona; Lundgren, Jesper; Abrahamsson, Kajsa H.
Abstract: Objectives: Adequate oral hygiene, that is self‐performed infection control, is crucial to prevent periodontal disease. Epidemiological studies reveal poor oral hygiene conditions among Swedish adolescents and indicate a need for more effective prevention programs. The aim of the current study was to analyse adolescents' experiences of a person‐centred, theory‐based, oral health education program for improved oral hygiene. Methods: Data were obtained by interviewing 19 adolescents treated by dental hygienists in accord with the person‐centred education program in a preceding clinical field study (ClinicalTrials.gov NCT02906098). Study participants were selected to reflect a variation of male and female adolescents, treated at clinics in areas with various socio‐demographic profiles within Region Västra Götaland, Sweden. Interviews were audio‐taped, transcribed verbatim and analysed with qualitative content analysis. Results: A main theme was identified: 'Adolescents on a guided and challenging journey towards beneficial oral hygiene behavior'. The results elucidate the importance of a person‐centred approach in therapy. The adolescents described insight on a personal level about the importance of improved oral hygiene as fundamental for behavioural change. Planning and monitoring of the behaviour, with guidance and support by the dental hygienist, was considered to facilitate change and encouraged further behavioural efforts. However, the adolescents expressed a need of reminders and support to keep up oral hygiene routines over time. Conclusions: The study brings knowledge on factors of importance in educational interventions to increase beneficial health behaviours among adolescents and emphasize areas for further improvements of such interventions.